2006
DOI: 10.1063/1.2337524
|View full text |Cite
|
Sign up to set email alerts
|

Charge-dipole model to compute the polarization of fullerenes

Abstract: The authors present a charge-dipole model for the calculation of the polarization of fullerenes and carbon nanotubes. By expressing the electrostatic interactions in terms of normalized propagators, the technique achieves a better consistency and an improved stability. In its most elementary form, the model depends on a single parameter and provides an excellent agreement with reference data. The technique is illustrated with a C720 fullerene and enables one to quantify the role of free charges in the polariza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 24 publications
1
51
0
Order By: Relevance
“…As to the heterogeneous microstructures, the oscillation of localized space charges at subnanometer scale interfaces is, therefore, considered a main contributor to the dielectric polarization phenomenon with similarities to a boundary layer capacitor [16][17][18][19][20][21][22]. Assuming all the NbC clusters are spherical in shape, one can estimate that the increased interface area for the ðNb þ NbCÞ=C composite is about 30% higher relative to the NbC=C composite.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As to the heterogeneous microstructures, the oscillation of localized space charges at subnanometer scale interfaces is, therefore, considered a main contributor to the dielectric polarization phenomenon with similarities to a boundary layer capacitor [16][17][18][19][20][21][22]. Assuming all the NbC clusters are spherical in shape, one can estimate that the increased interface area for the ðNb þ NbCÞ=C composite is about 30% higher relative to the NbC=C composite.…”
mentioning
confidence: 99%
“…Under an external electromagnetic field, this polarized charge oscillates at a specific time scale, resulting in a delayed response to the external field (see Fig. S2 and the discussion in the Supplemental Material [14]) [15,17,18].…”
mentioning
confidence: 99%
“…This work in turn was the basis for a series of publications including those by Ponder and co-workers (Ren & Ponder 2002Schnieders et al 2007), in which induced dipoles were used to study small-molecule systems and solvation effects. Indeed, the method of modelling polarization by explicit induced dipoles has been applied to models of a wide range of systems (Borodin & Smith 2006a,b;Mayer et al 2006), including force fields designed for protein systems (Wang et al 2006). Calculations by Baucom et al (2004) have demonstrated that this brings about a meaningful improvement in the modelling of a DNA strand.…”
Section: Equation (38) Is Solved By Rearranging Into the Formmentioning
confidence: 99%
“…[10][11][12] Dipole polarizability of the M 3 N@C 2n fullerenes have been studied by using density functional theory (DFT). [13][14][15] Unlike nonmetal endohedral fullerenes, M 3 N@C 2n show smaller dipole polarizability than the corresponding C 2n empty cage because the induced electric field of the carbon cage is reduced by inserting the M 3 N cluster. Functionalization of Sc 3 N@C 80 has been accomplished using both a Diels-Alder reaction and an azomethine ylide addition.…”
Section: Introductionmentioning
confidence: 99%